2005
DOI: 10.1016/j.ydbio.2005.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors sustain primordial germ cell survival, proliferation and entering into meiosis in the absence of somatic cells

Abstract: It is known that mammalian primordial germ cells (PGCs), the precursors of oocytes and prospermatogonia, depend for survival and proliferation on specific growth factors and other undetermined compounds. Adhesion to neighboring somatic cells is also believed to be crucial for preventing PGC apoptosis occurring when they lose appropriate cell to cell contacts. This explains the current impossibility to maintain isolated mouse PGCs in culture for periods longer than a few hours in the absence of suitable cell fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 25 publications
7
104
0
Order By: Relevance
“…These problems caused a decrease in the rate of formation and development of the primordial follicles. Researchers found that mouse oocytes derived from fetal germ cells were unable to resume meiosis and progress to the last stage of growth in vitro (Klinger & de Felici 2002, Obata et al 2002a, Niwa et al 2004, Farini et al 2005. The efforts to solve these problems with an in vitro culture system were limited because very little is known about the mechanisms underlying the initiation of oocyte growth, the molecular interactions between the oocytes and somatic cells during the follicle formation, the formation of gap junctions in the follicle, and the growth initiation and selective mechanisms of the follicle (Klinger & de Felici 2002, Lee et al 2002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems caused a decrease in the rate of formation and development of the primordial follicles. Researchers found that mouse oocytes derived from fetal germ cells were unable to resume meiosis and progress to the last stage of growth in vitro (Klinger & de Felici 2002, Obata et al 2002a, Niwa et al 2004, Farini et al 2005. The efforts to solve these problems with an in vitro culture system were limited because very little is known about the mechanisms underlying the initiation of oocyte growth, the molecular interactions between the oocytes and somatic cells during the follicle formation, the formation of gap junctions in the follicle, and the growth initiation and selective mechanisms of the follicle (Klinger & de Felici 2002, Lee et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…When the ovaries of newborn mice were cultured in vitro with whole organ for 8 days, and then the growing oocyte-granulosa cell complexes were isolated from the organ-cultured ovaries and cultured for an additional 14 days, these oocytes were able to be fertilized in vitro, and supported the development to term , O'Brien et al 2003. The culture conditions for purified mouse PGCs in the absence of somatic cell support had been established to study the molecular dissection of the processes governing the development of such cells crucial for early gametogenesis (Farini et al 2005). Under these culture conditions, PGCs were able to proliferate at high rate, undergo meiosis, and even to progress to a completed meiotic prophase I; however, they did not go on to grow and enter the meiotic prophase II.…”
Section: Discussionmentioning
confidence: 99%
“…24). A mixture of soluble growth factors [Kit ligand, leukemia inhibitory factor (LIF), BMP-4, stroma derived factor-1, bFGF] and compounds (N-acetyl-cysteine, forskolin, retinoic acid) were needed to sustain the survival and self-renewal of mouse PGCs in the absence of somatic cell support (38). Recently, long-term proliferation was reported for male germ-line stem cells of the mouse in the presence of glial cell line-derived neurotrophic factor, epidermal growth factor, bFGF, and LIF without any feeder cells (39).…”
Section: Characteristics Of Somatic Cells and Establishment Of A Somamentioning
confidence: 99%
“…In vivo, several growth factors are responsible for the differentiation of PGCs into oogonia after the arrival at the genital ridge. These include kit ligand (KL), bone morphogenic proteins (BMPs), stem cell factor (SCF), fibroblast growth factor (βFGF) and members of the transforming growth factor β (TGFβ) superfamily [11]. Several studies have established conditions by which ES cells generate germ cells in vitro through the use of PGC and germ cell enrichment techniques [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%